Pengaruh Model Pembelajaran Berbasis Masalah terhadap Kemampuan Literasi Sains Siswa pada Materi Sistem Ekskresi - Nabila Halim Nasution; Hasruddin, Hasruddin; Juliani, Juliani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aimed to investigate the effect of problem-based learning on students' science literacy skills in the excretory system material for grade 11 science students at Madrasah Aliyah Negeri Binjai. This research was a quasi-experimental study using a pretest-posttest nonequivalent control group design. The population of this study was all grade 11 science students at Madrasah Aliyah Negeri Binjai in the 2023/2024 academic year. Cluster sampling was used to obtain two classes as samples, namely the experimental class (XI MIA 2) and the control class (XI MIA 5). Data was collected using a science literacy test instrument consisting of 20 multiple-choice questions, developed based on the Programme for International Student Assessment (PISA) framework, which measures three science literacy competencies: explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and evidence scientifically. The results showed that the average post-test score of the experimental class (using PBL) was higher (81.67) compared to the control class (61.06). The Independent Sample T-test showed a significant difference between the two groups, so the null hypothesis was rejected and the alternative hypothesis was accepted. Based on these results, it can be concluded that PBL has a positive effect on improving students' science literacy skills in the excretory system material.